Implementing Kahoot in Teaching Mahārah Istimā‘ at Maskan Al-Lughah Al-‘Arabiyyah, Al-Ikhlas Dormitory - Rahmah, Siti; Nuruddaroini, M. Ahim Sulthan; Khafifah, Siti (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
In the digital era, Arabic language learning is required to be more innovative and interactive. However, most students still face challenges in improving their listening skills (mahārah al-istimā‘) because conventional teaching methods tend to be unengaging and lack interactivity. Therefore, there is a need for learning media that can increase student engagement, such as Kahoot, a digital game-based learning platform. This study aims to describe the implementation of Kahoot in mahārah al-istimā‘ instruction and to analyze its contribution to student motivation at the Al-Ikhlas Dormitory of STIQ Amuntai through the Maskan al-Lughah al-‘Arabiyyah program, which provides a fully Arabic-language environment.This study employed a descriptive qualitative approach in the form of a field study. Data were collected through observation, interviews, and documentation of three informants selected through purposive sampling. The results indicate that the implementation of Kahoot occurred in four stages: scheduling, technical briefing, conducting audio-based quizzes, and post-activity evaluation. Based on the results of interviews and observations, the use of Kahoot contributed positively to increasing participants’ motivation, enthusiasm, concentration, and engagement in listening to Arabic-language material, as demonstrated by increased active participation, focus while listening to audio, and positive responses during the activity. These findings align with the game-based learning approach, which emphasizes active student participation. The main constraint identified was internet connectivity issues. This study indicates that Kahoot can serve as an alternative learning medium that supports the development of listening skills in an Arabic-language environment.